Assessing the Economic Impact of Community Based Mangrove Ecotourism on Coastal Livelihoods in East Lombok - Herawati, Baiq Candra; Soraya, Siti (Target : Jurnal Manajemen Bisnis, 2025)
The concept of community-based ecotourism places local communities as the main actors in sus-tainable coastal resource management. This study aims to evaluate the economic impact of community- based mangrove ecotourism development on the welfare of coastal communities in Poton Bako Hamlet, East Lombok Regency, Indonesia. This study was motivated by implementing a community empower- ment program integrated with mangrove conservation activities and educational ecotourism development in 2024-2025. The research method used was a mixed-methods approach, with data collection through structured interviews with local stakeholders, analysis of Bale Mangrove Pokdarwis’ financial reports, and participatory observation of community-based tourism activities. The results of the study showed a significant increase in village income, with an accumulation of IDR 647.38 million until April 2025. Most of the income was allocated for social activities, environmental conservation, and the construction of public facilities. In addition, this program encourages the growth of new economic activities, creates job opportunities for young people, and encourages diversification of community livelihoods that previously depended on the traditional fisheries and agriculture sectors. The practical implications of this research indicate that community-based ecotourism, when supported by strong local institutions and participa- tory governance, has the potential to be a sustainable economic driver in remote coastal areas.